Yardstick competition, corruption, and electoral incentives - Ngo Van Long; Bodhisattva Sengupta (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper investigates the relationship between electoral incentives, institutions and corruption. We assume that voters use a yardstick criterion. The incumbent provides a public good and extracts rent, which are financed by imposing a distortionary tax. We demonstrate the possibility that yardstick competition itself fails to restrict rent seeking. We complement the static setting with a dynamic scenario where each incumbent politician faces an election after a finite, fixed term. Under relative performance evaluation, dynamic incentives impose more restriction on rent appropriation in comparison to the static case.
Keywords: H11; H73; H77; 330; Yardstick competition; rent-seeking; public good; electoral incentives; Yardstick Competition; Public Choice; Rent Seeking; Wahl; Ökonomischer Anreiz; Öffentliches Gut; Theorie